Embracing the Surface: How to Read a Life Narrative. (2nd January 2017) - Drake, Jennifer
ABSTRACT: To teach life narrative is to teach empathetic practice. This requires teaching students that life narrative employs specific writing techniques. Through the practice of "surface reading", students can take measure of their suitability for the role of addressee, or ideal listener, and calibrate their encounter with the text from there.